AB0193 THE EFFECTS OF NON-INVASIVE VAGUS NERVE STIMULATIONON FATIGUE AND NEUROCOGNITION IN PARTICIPANTS WITH PRIMARY SJÖGREN'S SYNDROME. (June 2019) - Tarn, Jessica; Macrae, Victoria; Mitchell, Sheryl; Simon, Bruce; Gallagher, Peter; Taylor, John-Paul; Watson, Stuart; Baker, Mark; Rushton, Stephen; Blamire, Andrew; Newton, Julia; Ng, Wan Fai
Abstract : Background: Primary Sjögren's syndrome (pSS) sufferers have rated physical and mental fatigue ('brain fog') as the most important symptoms needing improvement. Previous data from our group suggest that stimulation of the vagus nerve can invoke immunological responses and concurrently an improvement of patient reported symptoms of fatigue 1 . Objectives: This follow up study uses the gammaCore device (electroCore) and a sham device to assess the effects of non-invasive vagus nerve stimulation (nVNS) on patient reported symptoms of fatigue in pSS. In addition, neurocognitive tests were used to assess the effect of nVNS on short term memory, executive function and attention. Methods: 40 pSS participants were assigned to use active (n = 20) or sham (n = 20) nVNS devices. Participants and research staff were blinded to the active/sham device assignment. The participants were instructed to use the device twice daily for a study period of 56 days. The following patient reported measures of fatigue and neuropsychological tests were collected at baseline and day 56; Profile of Fatigue (PRO-F, Physical and Mental), visual analogue scale (VAS) of abnormal fatigue, trail making, Digit Symbol Substitution Test (DSST), Stroop test and digit span. 7 subjects were excluded from the analysis due to withdrawal from the study. Changes in fatigue and test scores from baseline to day 56 were compared between devices using t-tests. Results: Physical fatigue was significantly reduced between baseline and day 56 in the active group but not the placebo group (p = 0.047) The mean reduction in physical fatigue was 30% and 6% for the active and sham arms respectively (Figure 1 ). In both the active and sham subject groups there were no significant changes in the patient reported mental fatigue or neuropsychological test scores. Conclusion: This sham controlled scientific study of vagus nerve stimulation in pSS suggests nVNS may improve patient reported symptoms of physical fatigue, which is consistent with our published data. There were no improvements in the neurosychological test scores which is consistent with no improvements in patient reported mental fatigue. nVNS has been shown to activate the anti-inflammatory reflex, therefore assessment of peripheral inflammatory markers may help our understanding of nVNS, inflammation and fatigue. Reference: [1] Tarn, J., Legg, S., Mitchell, S., Simon, B. & Ng, W.-F. The Effects of Noninvasive Vagus Nerve Stimulation on Fatigue and Immune Responses in Patients With Primary Sjögren's Syndrome. Neuromodulation49, 844 (2018). Disclosure of Interests: Jessica Tarn: None declared, Victoria Macrae: None declared, Sheryl Mitchell: None declared, Bruce Simon Shareholder of: Bruce Simon is an employee and shareholder of electroCore., Peter Gallagher: None declared, John-Paul Taylor: None declared, Stuart Watson: None declared, Mark Baker: None declared, Stephen Rushton: None declared, Andrew Blamire: None declared, Julia Newton: None declared, Wan Fai Ng: None declared